Polarization Reversal in der Entwicklung brasilianischer Metropolen? Eine Analyse anhand demographischer Indikatoren am Beispiel von Sao Paulo - Bähr, Jürgen; Wehrhahn, Rainer (ERDKUNDE, 1995)
Using the example of Sao Paulo, this paper addresses itself to the question of how far the decrease in growth rates one observes in large Brazilian metropolises can be interpreted as a process of polarization reversal. The analysis is carried out on the basis of demographic data from small area units, which include the results from the most recent 1991 census. Although it had already been possible in the 1970s to discern first indications of such a process setting in, in the decade 1981-91 indicators of population growth and migration balances agree in pointing to a polarization reversal. This means that in the case of the federal state of Sao Paulo the development centres on the periphery are gaining whereas the Metropolitan region is losing. In the same cases there is even already evidence of intraregional decentralization in the area surrounding the new subcentres. This development has been significantly promoted by improvements in the infrastructure, modernization of agriculture, the construction of some modern technical-industrial locations as well as by disadvantages of agglomeration in Sao Paulo, which gradually make themselves felt. But there has not at any time been an active policy of decentralization. It is, however, not possible to transfer the results from the federal state of Sao Paulo to Brazil as a whole. Though demographic indicators are pointing to the onset of a polarization reversal at national level, as on the whole the peripheral inland areas tend to profit more from population increases than the coastal areas, the development cannot be reconstructed by the economic data. It seems rather that there is some reason to believe that the economic dominance of the South and the Southeast will persist.